Diagnostic potential of dentatorubrothalamic tract analysis in progressive supranuclear palsy - Seki, Morinobu; Seppi, Klaus; Mueller, Christoph; Potrusil, Thomas; Goebel, Georg; Reiter, Eva; Nocker, Michael; Steiger, Ruth; Wildauer, Matthias; Gizewski, Elke R.; Wenning, Gregor K.; Poewe, Werner; et al. (Parkinsonism & related disorders, 2018)
The differentiation of progressive supranuclear palsy-parkinsonism (PSP-P) from Parkinson's disease (PD) remains a major clinical challenge. To evaluate the diagnostic potential of observer-independent assessments of microstructural integrity within infratentorial brain regions to differentiate PSP-Richardson's syndrome (PSP-RS), PSP-P and PD. 3T MRI parameters of mean diffusivity, fractional anisotropy, grey and white matter volumes from patients with PSP-RS (n = 12), PSP-P (n = 12) and mean disease duration of 2.4 ± 1.7 years were compared with PD patients (n = 20) and healthy controls (n = 23) by using statistical parametric mapping and the spatially unbiased infratentorial template. Subsequently MRI measurements of the dentatorubrothalamic tract were determined observer-independently by a validated probabilistic infratentorial atlas. The impairment of gait and postural stability was evaluated by a sum-score derived from the Unified Parkinson Disease Rating Scale. Significant mean diffusivity increases, fractional anisotropy decreases and corresponding volume loss were localized in mesencephalic tegmentum, superior cerebellar peduncle, decussation of superior cerebellar peduncle and dentate nucleus in PSP-RS and PSP-P compared to PD and healthy controls. Altered microstructural integrity of the dentatorubrothalamic tract in PSP-RS was significantly more pronounced compared to PSP-P and correlated significantly with the gait and postural stability sum-score. Linear discriminant analysis identified diffusion tensor imaging measures of the dentatorubrothalamic tract and the gait and postural stability sum-score to classify correctly 95.5% of PRP-RS, PSP-P and PD patients. Observer-independent analysis of microstructural integrity within the dentatorubrothalamic tract in combination with assessments of gait and postural stability differentiate PSP-P from PSP-RS and PD in early to moderately advanced stages. •We applied voxel-based and atlas-based ROI analyses to MRI in PSP-RS, PSP-P and PD.•Both PSP subtypes showed altered DTI within the dentatorubrothalamic tract (DRTT).•PSP-RS demonstrated more pronounced DTI changes in the DRTT compared to PSP-P.•DTI of DRTT correlated with impairments of gait and postural stability in PSP-RS.•DTI of DRTT and gait and postural stability score could classify 95% of patients.